Development of fiber-based supercontinuum light sources for the biosensor and bio-imaging applications - Tang, Dingyuan. (2008)
In the project we have systematically investigated the core technology related to the fiber-based SC light sources, these include the development of the NLP fiber laser sources, the design and development of a superbroad NLP laser source, the development of soliton and NLP fiber laser sources in the normal dispersion region, and the development of a fiber laser source that can generate ultrashort pulses with ultrahigh peak power and superbroad bandwidth beyond the gain-bandwidth limitation. For the NLP fiber lasers operated in the anomalous dispersion region, we have experimentally investigated the dispersion managed fiber lasers and the conventional fiber lasers.